Transnational community and communicative interaction: social diagnosis - Chávez-Torres, Guillermina; Preciado-Jiménez, Susana Aurelia (Prospectiva. Revista de Trabajo Social e Intervención Social, 2018)
This article is reflection made from the Social Work perspective in order to present a social diagnosis associated with a transnational community that has been configured between Mexico and the United States. This diagnosis is constructed through the information that the tamazulense community (native of Tamazula de Gordiano) who is resident in the United States brought through the observations and interviews made. This is a case of study of the online communicative interaction used by the transnational community, looking forward to generates close, constant and daily links between the "here and there" population, in other words, keeping the population together in the distance.Most probably, the communicative interaction studied using virtual ethnography aims to generate useful information of a theoretical-methodological nature, in order to generate a binational intervention project as an opportunity for collaboration between disciplines on the subject of migration policies, as well as their participation in programs developed in consular offices for the attention of compatriots.